Responses of symbiotic nitrogen-fixing common bean to aluminum toxicity and delineation of nodule responsive microRNAs - Mendoza-Soto, Ana B.; Naya, Loreto; Leija, Alfonso; Hernández, Georgina (Frontiers in Plant Science, 2015)
Aluminum (Al) toxicity is widespread in acidic soils where the common bean (Phaseolus vulgaris), the most important legume for human consumption, is produced and it is a limiting factor for crop production and symbiotic nitrogen fixation. We characterized the nodule responses of common bean plants inoculated with Rhizobioum tropici CIAT899 and the root responses of nitrate-fertilized plants exposed to excess Al in low pH, for long or short periods. A 43 - 50% reduction in nitrogenase activity indicates that Al toxicity highly affected nitrogen fixation in common bean. Bean roots and nodules showed characteristic symptoms for Al toxicity. In mature nodules Al accumulation and lipoperoxidation were observed in the infected zone, while callose deposition and cell death occurred mainly in the nodule cortex. Regulatory mechanisms of plant responses to metal toxicity involve microRNAs (miRNAs) along other regulators. Using a miRNA-macroarray hybridization approach we identified 28 (14 up-regulated) Al toxicity nodule-responsive miRNAs. We validated (qRT-PCR) the expression of eight nodule responsive miRNAs in roots and in nodules exposed to high Al for long or short periods. The inverse correlation between the target and miRNA expression ratio (stress:control) was observed in every case. Generally, miRNAs showed a higher earlier response in roots than in nodules. Some of the common bean Alt responsive miRNAs identified have also been reported as differentially expressed in other plant species subjected to similar stress condition. miRNA/target nodes analyzed in this work are known to be involved in relevant signaling pathways, thus we propose that the participation of miR164/NAC1 and miR393/TIR1 in auxin and of miR170/SCL in gibberellin signaling is relevant for common bean response/adaptation to Al stress. Our data provide a foundation for evaluating the individual roles of miRNAs in the response of common bean nodules to Al toxicity.